2021
DOI: 10.1155/2021/6693895
|View full text |Cite
|
Sign up to set email alerts
|

Getting to the Heart of the Matter: Myocardial Injury, Coagulopathy, and Other Potential Cardiovascular Implications of COVID-19

Abstract: COVID-19 was primarily identified as a respiratory illness, but reports of patients presenting initially with cardiovascular complaints are rapidly emerging. Many patients also develop cardiovascular complications during and after COVID-19 infection. Underlying cardiovascular disease increases the severity of COVID-19 infection; however, it is unclear if COVID-19 increases the risk of or causes cardiovascular complications in patients without preexisting cardiovascular disease. The review is aimed at informing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 122 publications
0
8
0
2
Order By: Relevance
“…The cardiac manifestations that may occur during COVID-19 infection include acute cardiac injury, myocarditis, acute myocardial infarction (AMI), heart failure, arrhythmia, cardiomyopathy, hypotension, shock, and cardiac arrest (18,23,24). An echocardiographic study of patients with COVID-19 documented pre-existing abnormalities, which prompted the authors to suggest caution with regard to attributing such abnormalities to acute COVID-19 infection (25).…”
Section: The Clinical Aspects Of Covid-19 and Cardiovascular Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…The cardiac manifestations that may occur during COVID-19 infection include acute cardiac injury, myocarditis, acute myocardial infarction (AMI), heart failure, arrhythmia, cardiomyopathy, hypotension, shock, and cardiac arrest (18,23,24). An echocardiographic study of patients with COVID-19 documented pre-existing abnormalities, which prompted the authors to suggest caution with regard to attributing such abnormalities to acute COVID-19 infection (25).…”
Section: The Clinical Aspects Of Covid-19 and Cardiovascular Diseasementioning
confidence: 99%
“…An echocardiographic study of patients with COVID-19 documented pre-existing abnormalities, which prompted the authors to suggest caution with regard to attributing such abnormalities to acute COVID-19 infection (25). Among the vascular complications documented are venous and arterial thrombotic events, which are associated with greater need for respiratory support, vasopressors, and hemodialysis, and a longer hospital stay (24,26). Autopsy studies from patients who died from COVID-19 infection have demonstrated a range of cardiac abnormalities including cardiac hypertrophy and/or enlargement, ventricular dilatation, infarction, and fibrosis (24).…”
Section: The Clinical Aspects Of Covid-19 and Cardiovascular Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Coronavirus 19 disease 2019 (COVID-19), associated with SARS-CoV-2 virus pandemic, leads to a significant increase in the risk of death, mainly affecting elderly people with chronic diseases including diabetes [1] , [2] , [3] , [4] , [5] . Moreover, COVID-19 shares with diabetes an increased risk of thrombotic or thromboembolic events leading to acute cardiovascular events [6] , [7] , [8] , [9] , [10] . In addition, mortality linked to diabetes or to incident myocardial infarctions are significantly augmented during COVID-19 acute manifestations [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%